HASRAT PENGARANG DALAM NOVEL SALAH ASUHAN KARYA ABDOEL MOEIS (KAJIAN PSIKOANALISIS LACAN) (The Author’s Desire in the Novel Salah Asuhan by Abdoel Moeis: Lacan’s Psychoanalysis Study) - Jafar Lantowa (Balai Bahasa Sulawesi Selatan, 2022)
In the novel Salah Asuhan, Hanafi lives the span of his life with the strength of his desire to be a different person. This character is a representative of the author's voice on his various experiences in associating with Europeans. This study aims to describe the author's desire manifested in the novel Salah Asuhan, both the “desire to be” and the “desire to have.” This study employed qualitative research methods. Data were analyzed using Lacanian psychoanalytic method. The results show that through Hanafi's character, it is clear that the author's desire is to be European and to have European attributes.For the author, the desire to be European is actually to reject the Dutch discrimination against the East. Abdul Muis as the author wants to dress in European style because of the education he received in Europe. However, this desire is opposed by the Europeans.This opposition shows discrimination against natives. Therefore, this novel is a critique of European discrimination against natives, while the Hanafi character actually suggests that a native should still recognize himself as an Easterner.